1995
DOI: 10.1083/jcb.130.5.1219
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of two basement membrane collagen genes, COL4A6 and COL4A5, demonstrated by immunofluorescence staining using peptide-specific monoclonal antibodies.

Abstract: Genes for the human alpha 5(IV) and alpha 6(IV) collagen chains have a unique arrangement in that they are colocalized on chromosome Xq22 in a head-to-head fashion and appear to share a common bidirectional promoter. In addition we reported a novel observation that the COL4A6 gene is transcribed from two alternative promoters in a tissue-specific manner (Sugimoto, M., T. Oohashi, and Y. Ninomiya. 1994. Proc. Natl. Acad. Sci. USA. 91:11679-11683). To know whether the translation products of both genes are coloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
259
1
2

Year Published

1996
1996
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(271 citation statements)
references
References 45 publications
9
259
1
2
Order By: Relevance
“…Monoclonal antibodies against the NC1 domain of the ␣4 chain of type IV collagen (mAb 85) (22) were a gift from MM Kleppel, (22) and monoclonal antibodies against the NC1 domain of the ␣6(IV) chain (H63) were from Y Sado. 23 Affinity-purified fluorescein isothiocyanate-conjugated sheep immunoglobulin G anti-rabbit and anti-mouse immunoglobulins were from Silenius (Victoria, Australia). Fluorescein-conjugated affinity-purified donkey antisheep immunoglobulin G (HϩL) antibodies were from Jackson Laboratories (West Grove, PA).…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Monoclonal antibodies against the NC1 domain of the ␣4 chain of type IV collagen (mAb 85) (22) were a gift from MM Kleppel, (22) and monoclonal antibodies against the NC1 domain of the ␣6(IV) chain (H63) were from Y Sado. 23 Affinity-purified fluorescein isothiocyanate-conjugated sheep immunoglobulin G anti-rabbit and anti-mouse immunoglobulins were from Silenius (Victoria, Australia). Fluorescein-conjugated affinity-purified donkey antisheep immunoglobulin G (HϩL) antibodies were from Jackson Laboratories (West Grove, PA).…”
Section: Patientsmentioning
confidence: 99%
“…In the human and rodent kidney, immunohistochemical studies have shown a low-level expression of ␣1(IV) to ␣2(IV) in mature GBM whereas the ␣3(IV) to ␣5(IV) chains are highly expressed. [22][23][24][25][26][27] Little is known about the different isoforms of triple-helical type IV collagen molecules, 5,28 and their supramolecular organization in the different basement membranes. However, different subpopulations of NC1 hexamers, which reflect the association of two triple-helical molecules within the type IV collagen network, have been described recently in GBM as well as in other basement membranes.…”
mentioning
confidence: 99%
“…It has been shown that 3(IV)-and 4(IV)-chains co-localize and are only present in specialized basement membranes, for example in the kidney, eye, cochlea, lung and brain, whereas the 1(IV)-and 2(IV)-chains are present in all basement membranes [6]. Results show that the 5(IV)-and 6(IV)-chains also have a limited distribution in different basement membranes [5,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In most patients with Alport syndrome, the GBM contains the ␣1 and ␣2 chains and lacks the ␣3, ␣4, and ␣5 chains. 8,9,14,15 The altered ␣-chain composition seems to reflect an arrest of an early developmental switch, wherein an immature ␣1/␣2 network persists and is not replaced by the ␣3/␣4/␣5 network. 10,16 The existence of an ␣3/␣4/␣5 network provides a plausible explanation for the absence of these chains in Alport syndrome in the setting of COL4A3, COL4A4, or COL4A5 mutations, in that all three chains are required for the assembly of this network.…”
mentioning
confidence: 99%
“…Type IV collagen is assembled from a family of distinct ␣-chains designated ␣1 to ␣6, which are encoded by six different genes, COL4A1 to COL4A6, respectively. 7 The glomerular basement membrane (GBM) is composed of the ␣1 to ␣5 chains, 8,9 which are assembled in triple helices that in turn selfassemble into supramolecular networks. Two distinct ␣1/ ␣2-containing and ␣3/␣4/␣5-containing networks have been identified at the biochemical level.…”
mentioning
confidence: 99%